Nanostructured Lipid Carriers as Robust Systems for Lupeol Delivery in the Treatment of Experimental Visceral Leishmaniasis - Jesus, Jéssica Adriana [UNESP] (2023)
Leishmaniasis is a neglected tropical disease that affects millions of people around the world. Available therapy causes severe side effects, has unacceptable prices for some specific formulations, and the existence of drug-resistant parasites limits the use of the currently available arsenal of antiparasitic drugs. Therefore, natural products serve as one of the main sources to develop new and effective alternative drugs against leishmaniasis. In this sense, the present study evaluated the potential of the triterpene Lupeol (Lu) entrapped in nanostructured lipid carriers (NLCs) for the treatment of experimental visceral leishmaniasis. The therapeutic efficacy of Lu or Lu entrapped in NLC (Lu-NLC) was investigated in golden hamsters infected with Leishmania (Leishmania) infantum. Lu-NLC presented a mean particle size of 265.3 ± 4.6 nm, a polydispersity index of <0.25 and a zeta potential of −37.2 ± 0.84 mV; the efficacy of encapsulation was 84.04 ± 0.57%. Studies on hamsters showed that Lu-NLC (5 mg/kg) administered intraperitoneally for 10 consecutive days caused a reduction of 99.9% in the number of parasites in the spleen and liver compared to the untreated infected control. On the contrary, Lu-treated animals (5 mg/kg) had 94.4 and 90.2% less parasites in the spleen and liver, respectively, than the infected group. Additionally, a significant preservation of splenic and hepatic tissues was observed in animals treated with Lu-NLC or Lu. Furthermore, Lu-NLC-treated animals produced high levels of anti-Leishmania IgG2 isotype. These data indicate that NLC potentialized Lu efficacy in experimental visceral leishmaniasis. This work suggests that Lu and nanoformulations carrying this compound may be considered as an important tool to be included in the alternative therapy of leishmaniasis.